Children's literature as a means of pedagogical influence on the way to the emotional intelligence development of preschool children - Rudnytska-Yuriichuk, Iryna; Zhurat, Yuliya (Thoth Publishing House, 2025)
The article provides a theoretical analysis of the fiction influence on the emotional intelligence and creative imagination development of preschool children. The paper reveals the peculiarities of the relationship between fairy tale therapy and emotional intelligence, which are developed in preschoolers together with reflection and creative potential. The study describes the adult’s expediency giving examples of their own behaviour in various life situations when communicating with children. It is revealed that the process of developing emotional intelligence has its own characteristics, but its main structural elements begin to develop in older preschool age and are improved throughout the entire school period of study. The focus is on the fundamentals of emotional intelligence development as one of the key elements of the development of preschoolers' imagination, which include children's fiction, stories, and fairy tales. It is proven that the development of emotional potential in preschool age will help regulate their own mood and behaviour, teach how to cooperate with adults and peers.
Keywords: children's literature; empathy; emotional intelligence; fairy tale therapy; reflection; self- awareness; self-regulation; socialization